2018
DOI: 10.2217/cns-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Estimated lifetime survival benefit of tumor treating fields and temozolomide for newly diagnosed glioblastoma patients

Abstract: Aim:To estimate the mean lifetime survival benefit, an essential component of health economic evaluations in oncology, of adding tumor treating fields (TTFields) to maintenance temozolomide (TMZ) for newly diagnosed glioblastoma patients.Methods:We integrated EF-14 trial data with glioblastoma epidemiology data. The model provided for an evidence-based approach to estimate lifetime survival for the material number of EF-14 trial patients still alive at 5 years.Results & conclusion:Patients treated with TTField… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Bernard-Arnoux et al 39 estimated GBM survival using exponential extrapolation of median EF-14 survival rates. We previously observed this approach to be a poor visual fit to the actual EF-14 K-M survival curves, and that the exponential extrapolation had the worst fit of four estimated parametric approaches according to Akaike's information criterion testing 19 ; the Bernard-Arnoux et al 39 study consequently estimated that the TTFields and TMZ arm and TMZ alone arm converged by year-5, which was not observed in the trial.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Bernard-Arnoux et al 39 estimated GBM survival using exponential extrapolation of median EF-14 survival rates. We previously observed this approach to be a poor visual fit to the actual EF-14 K-M survival curves, and that the exponential extrapolation had the worst fit of four estimated parametric approaches according to Akaike's information criterion testing 19 ; the Bernard-Arnoux et al 39 study consequently estimated that the TTFields and TMZ arm and TMZ alone arm converged by year-5, which was not observed in the trial.…”
Section: Discussionmentioning
confidence: 93%
“…Our literature review of long-term GBM OS has been described previously 19 . Given the material number of 5-year survivors in the EF-14 trial, we reviewed epidemiological literature reporting long-term GBM survival to determine the best modeling approach to extrapolate the EF-14 survival curves.…”
Section: Epidemiology Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to relatively small numbers of 3-year survivors, a 3-year survival rate could not be estimated reliably for TTFields-treated patients [99]. Integrating EF-14 trial data with glioblastoma epidemiology data, Guzauskas et al estimated the conditional survival rates at 3, 5, 10, and 15 years for the EF-14 trial patients alive at year 2 [100]. The authors concluded that patients alive at year 2 after starting TTFields with adjuvant TMZ had 59.6%, 29.4%, 20.7%, and 17.4% probability of surviving to year 3, 5, 10, and 15 versus 53.1%, 14.7%, 10.3%, and 8.7% probability of surviving for patients alive at year 2 after starting maintenance TMZ only [100].…”
Section: Standard Therapy For Adult Glioblastoma: 15 Years Of Expementioning
confidence: 99%